Management of diseases in Norwegian Christmas tree plantations. Issue 8 (16th November 2020) - Talgø, Venche; Stensvand, Arne; Pettersson, Martin; Fløistad, Inger Sundheim
ABSTRACT: In integrated pest management (IPM), the goal is to keep the impact of damaging agents below a threshold level with reduced pesticide use. The present review is focusing on IPM of fungal diseases and Phytophthora root rot in Norwegian Christmas tree plantations. Healthy transplants are of vital importance to give the production a good establishment. Sanitation of diseased material and weeds is also very important in IPM. Management strategies will vary with the disease-causing agent in question, therefore, correct identification is necessary. The major pathogens are within the kingdom's Fungi (e.g. Neonectria neomacrospora ) and Chromista (e.g. Phytophthora spp.). They depend on relatively high humidity or free moisture to spread and infect. Any factors diminishing the duration of wet conditions will, therefore, reduce the disease pressure. Efficient weed management in Christmas tree fields will increase air circulation and thereby ensure a quicker drying after precipitation. Furthermore, certain weed species are host plants for rust fungi on Christmas trees, and thus, removal of the alternate host is a highly relevant control strategy. In Norway, fungicide use in Christmas trees is limited and only recommended during the short period from bud break to fully elongated shoots, generally the most vulnerable period concerning fungal attacks.